ANALISIS TERHADAP KEWENANGAN MAHKAMAH SYARIAH DALAM PENYELESAIAN SENGKETA EKONOMI SYARIAH - Sayid Anshar; Baso Ifing; Ronaldo Ronaldo (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
As a Muslim country, Indonesia has two different legal systems, civil law and Sharia law. In the economic context, Sharia law plays an important role in guiding transactions and economic activities of Indonesian Muslim population.In recent decades, more and more countries around the world have adopted and implemented sharia-appropriate economic systems. The development of such systems typically combines Islamic economic principles such as the prohibition of interest and speculation and the provision of zakat or charity systems. Data compilation uses a qualitative approach that can be used to analyze the authority of Sharia courts in resolving Sharia economic disputes. This approach aims to understand phenomena or events as they occur by exploring and analyzing data generated from journals, books and other articles. Collect data from relevant sources such as legal documents, Sharia court decisions, etc. Analyze the data collected by giving meaning and explaining it using a variety of relevant theories. Shariah is based on the sources of Islamic law, which is the Qur’an, Hadith, Ijma (consensus of the believers), and Qiyas. (analogi). These sources of law form the basis for the establishment of the law applied by the Sharia Court. The Law of Sharia economic events is the legal body that regulates the settlement of disputes, the submission of claims for rights, their inspection and decision, and the execution of judgments, as well as the enforcement of Syariah economic law.